2021
DOI: 10.1016/j.neuroimage.2021.118284
|View full text |Cite
|
Sign up to set email alerts
|

Intra-session test-retest reliability of functional connectivity in infants

Abstract: Resting functional MRI studies of the infant brain are increasingly becoming an important tool in developmental neuroscience. Whereas the test-retest reliability of functional connectivity (FC) measures derived from resting fMRI data have been characterized in the adult and child brain, similar assessments have not been conducted in infants. In this study, we examined the intra-session test-retest reliability of FC measures from 119 infant brain MRI scans from four neurodevelopmental studies. We investigated e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
(81 reference statements)
2
11
0
Order By: Relevance
“…The test-retest reliability for single edges (i.e., individual connections), however, was low as shown by low average edge-level intra-class correlations (mean ICC = 0.20, SD = 0.13). This follows previous reports on low univariate reliability of single functional connections for infants ( Dufford et al, 2021 , Wang et al, 2021a ) and adults ( Noble et al, 2019 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The test-retest reliability for single edges (i.e., individual connections), however, was low as shown by low average edge-level intra-class correlations (mean ICC = 0.20, SD = 0.13). This follows previous reports on low univariate reliability of single functional connections for infants ( Dufford et al, 2021 , Wang et al, 2021a ) and adults ( Noble et al, 2019 ).…”
Section: Resultssupporting
confidence: 90%
“…To assess the stability and uniqueness of rsFC in our sample, we compared connectivity patterns calculated from two approximately 4-minute splits of fMRI data after rigorous motion exclusion and quality control. We found relatively stable FC multivariate patterns (split-half r = 0.5), which aligns with the medium intra-session reliability of rsFC in newborn infants reported by ( Wang et al, 2021a ). Single-edge ICC were low, however, which follows previous studies ( Noble et al, 2019 , Dufford et al, 2021 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Numerous studies have proven that scan length is one of the key parameters in the design of MRI scanning that plays an important role in generating robust and stable results, particularly in experiments where candidates are anesthetized or have difficulty staying during scanning. They have reported the appropriate scan duration to achieve a stable brain's functional connectivity in the wakeful state (Wang et al, 2011 , 2021 ; Birn et al, 2013 ; Liao et al, 2013 ; Mejia et al, 2018 ; Teeuw et al, 2021 ). For instance, Birn et al ( 2013 ) showed that the test–retest reliability of FC can be significantly improved by increasing the duration of scanning to 9–13 min or longer (Birn et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, despite its potential, rs-fMRI suffers from significant variabilities involved in the BOLD signal that may cause difficulties in the replication of results across studies (Mason et al, 2007 ; Patriat et al, 2013 ). Several factors can contribute to the intra-subject variabilities and affect the reliability of estimated brain FC including head motion, physiological noise such as cardiac and respiratory effects, MRI acquisition parameters, and data analysis/standardization strategies (Birn, 2012 ; Guo et al, 2012 ; Zuo and Xing, 2014 ; Finn et al, 2017 ; Parkes et al, 2018 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%